Transnasal flow reduction in endovascular treatment for anterior cranial fossa dural arteriovenous fistula. Issue 10 (20th October 2020) - Kawabata, Shuhei; Nakamura, Hajime; Nishida, Takeo; Takagaki, Masatoshi; Izutsu, Nobuyuki; Takenaka, Tomofumi; Terada, Eisaku; Oshino, Satoru; Kishima, Haruhiko
ABSTRACT: Transarterial embolization (TAE) is a useful option for anterior cranial fossa–dural arteriovenous fistula (ACF–dAVF) as endovascular devices have progressed. Liquid agents are usually injected via a microcatheter positioned just proximal to the shunt pouch beyond the ophthalmic artery; however, high blood flow from the internal maxillary artery (IMA) often impedes penetration of embolic materials into the shunt pouch. Therefore, reducing blood flow from the IMA before embolization can increase the success rate. In the present case, to reduce blood flow from branches of the IMA, we inserted surgical gauze infiltrated with xylocaine and epinephrine into bilateral nasal cavities. Using this method, we achieved curative TAE with minimal damage to the nasal mucosa. Transnasal flow reduction is an easy, effective and minimally invasive method. This method should be considered in the endovascular treatment of ACF–dAVF, especially in patients with high blood flow from theIMA.